2017
DOI: 10.1088/1748-9326/aa5987
|View full text |Cite
|
Sign up to set email alerts
|

Public health impacts of excess NO x emissions from Volkswagen diesel passenger vehicles in Germany

Abstract: In September 2015, the Volkswagen Group (VW) admitted the use of 'defeat devices' designed to lower emissions measured during VW vehicle testing for regulatory purposes. Globally, 11 million cars sold between 2008 and 2015 are affected, including about 2.6 million in Germany. On-road emissions tests have yielded mean on-road NO x emissions for these cars of 0.85 g km À1 , over four times the applicable European limit of 0.18 g km À1 . This study estimates the human health impacts and costs associated with exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 33 publications
0
34
0
1
Order By: Relevance
“…As a result, the effects on health in Europe should be much larger than that calculated for the US (Hou et al 2016). Chossière et al (2017) have calculated the effects of excess NO x emissions from VW-only diesel passenger vehicles in Germany, and found that these vehicles have resulted in about 1200 premature deaths integrated over the sales period 2008-2015 in Germany and neighbouring countries. However, large discrepancies between test cycle NO x emissions and on-road emissions have been found across all manufacturers (UK Department for Transport 2016, Transport andEnvironment 2016).…”
Section: Introductionmentioning
confidence: 98%
“…As a result, the effects on health in Europe should be much larger than that calculated for the US (Hou et al 2016). Chossière et al (2017) have calculated the effects of excess NO x emissions from VW-only diesel passenger vehicles in Germany, and found that these vehicles have resulted in about 1200 premature deaths integrated over the sales period 2008-2015 in Germany and neighbouring countries. However, large discrepancies between test cycle NO x emissions and on-road emissions have been found across all manufacturers (UK Department for Transport 2016, Transport andEnvironment 2016).…”
Section: Introductionmentioning
confidence: 98%
“…vehicle speed, acceleration, and engine temperature) [62]. While most previous analyses make assumptions for NO x emissions to discern the impacts on air quality from defeat devices [29][30][31]35], we use directly measured emission data to study climate impacts, which are influenced by many relevant gases and aerosols. There are other emission data for diesel vehicles obtained from on-road measurements [8].…”
Section: Emission Datamentioning
confidence: 99%
“…For the particular VW case, human health studies estimated that the diesel vehicles with sophisticated software deployed have caused or will have caused a small, but positive number of deaths in the US: early deaths of approximately 59 persons with a 95% range of 4.6 to 130 during the violation period of 2008-2015 [29], 46 persons with a one sigma range of 40 to 52 for the same period [30], 5 to 50 persons per year [31], 59.2 persons during the violation period [20], and 12 persons for the same period (only in California) [32] (note that the limited treatments of uncertainties have been in dispute [33,34]). There are also a few studies investigating the health impacts in Europe [20,35,36]. From the climate perspective, this issue has been raised prior to the Paris Agreement [37] without however being substantiated by any quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published recently investigating the effect of NO x emissions from diesel vehicles, in some cases due to the VW emissions control defeat device, on air pollution and the implications for human health and social cost in the United States (Barrett et al 2015, Holland et al 2016, Wang et al 2016 and Europe (Brand 2016, Chossiere et al 2017, as well as addressing the issues more generally (Rojas-Rueda and Turner 2016). The studies focused on the US estimate that 46 and 59 excess deaths and ca.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, one study evaluated the effects for California and found that the additional 'hidden' NO x emissions (difference between the actual on-road NO x emission factor and the testing emission factor) would result in 12 excess deaths during the same 2009-2015 time period as the US studies, with the majority of the increase in mortality in metropolitan areas (Wang et al 2016). In work that parallels the US study by Barrett et al (2015), Chossiere et al (2017) estimated the cost of excess NO x emissions from VW vehicles in Germany to be 1200 premature deaths (1.9 billion EUR) in Europe. The study by Brand (2016) highlights the potential trade-offs between human health and climate change mitigation in policies related to diesel vehicles in the UK (not just those affected by the defeat device), showing that the excess NO x emissions from diesel vehicles are significant and that the benefit to air quality in reducing these emissions would be much larger and outweigh any of the few potential carbon disbenefits, based on a comparison of damage costs.…”
Section: Introductionmentioning
confidence: 99%